Depressive symptoms decrease health-related quality of life of patients with coronary artery disease and diabetes: a 12-month follow up study in primary care - Nina Tusa; Hannu Kautiainen; Pia Elfving; Sanna Sinikallio; Pekka Mäntyselkä (Taylor & Francis Group, 2023)
AbstractObjective Health-related quality of life (HRQoL) is a multidimensional patient-related outcome. Less is known about the role of depressive symptoms on HRQoL in chronic diseases. This follow-up study analyzed depressive symptoms' association with HRQoL change measured with 15D in patients with chronic diseases.Design and setting A total of 587 patients from the Siilinjärvi Health Center, Finland were followed up due to the treatment of hypertension (HA), coronary artery disease (CAD) or diabetes (DM). Depressive symptoms were based on Beck Depression Inventory (BDI) (BDI ≥10 =depressive symptoms). HRQoL was assessed at the baseline and after 12 months.Results There were 244 patients with HA (mean age 70 years, 59% women); 103 patients (72 years, 38%) with CAD and 240 with DM (67 years, 52%). The change from baseline to the 12-month follow-up in 15D was significantly different between patients without and with depressive symptoms in CAD (p < 0.001) and DM (p = 0.024). In CAD with depressive symptoms, the change was −0.064 (95% CI: −0.094 to −0.035) and in DM −0.018 (95% CI: −0.037 to 0.001). In the 15 HRQoL dimensions of 15D, a depressive symptoms-related decrease was found in three dimensions with HA, in 9 with CAD and in 7 with DM. As a function of the BDI at baseline, the 15D score decreased significantly among patients with CAD and DM.Conclusions Depressive symptoms impact negatively on future HRQoL among primary care patients with coronary artery disease and diabetes emphasizing that mood should be acknowledged in their care and follow-up.Trial registration Clinical Trials registration number: NCT02992431, registered December 14th 2016